Education Is the Key to Prosperity: The Barbadian Education System and 20th-Century Black Barbadian Migrants in Canada - Taylor, Christopher Stuart (Sage Publications, Inc., 2014)
The following article will discuss the history of formal education in Barbados and will situate how this emphasis on the equal access to education between the sexes facilitated the emigration of Black Barbadian educators, most notably Black women, in the mid-20th century. This article argues that the emphasis on education was a deliberate and calculated initiative by the Barbadian Government to assist in the socio-economic advancement of its Black population up to the mid-20th century. The author has chosen this period to reflect the mass emigration of Black Barbadians to Canada prior to liberalization of the latter's immigration policies in the late 1960s and beyond. The article highlights that female and male Black Barbadian migrants capitalized on their educational background to circumvent and challenge racist international migration barriers. Moreover, the following will situate Black Barbadian educators in Canada in the 1950s and 1960s.
Keywords: Barbados; Canada; black migrants; gender; education; race